Forceps biopsy in the diagnosis of intrabronchial neoplasmatic lesions - Piorunek, Tomasz; Młynarczyk, Witold; Nowicka, Agata; Goździk, Joanna; Skowronek, Janusz; Kanikowski, Marek (Contemporary Oncology/Współczesna Onkologia, 2005)
The study was performed in 1996-2003 on a group of 585 patients who underwent fiberoptic bronchoscopy because of primary lung cancer suspicion. A tentative diagnosis was made on the basis of the patient history and lesions identified in conventional chest X-ray pictures. Symptoms of the neoplasmatic disease were caused by infiltration of the respiratory system, by metastases in lymph nodes and distant organs or were constitutional symptoms. Chest X-ray pictures revealed densities of lung fields suggesting neoplasmatic process, enlargement of hila or superior mediastinum, signs of atelectasis or pleural effusion or elevated hemidiaphragm. The aim of fiberoptic bronchoscopy was to state the location and type of growth, and to collect biopsy specimens for histopathological investigation from intrabronchial tumor or mucous membrane in a place of compressed or deformed bronchus. Basing on fiberoptic bronchoscopy conditions 1 to 4 specimens were taken. The aim of this study was to assess the usefulness of forceps biopsy in the diagnostics of intrabronchial neoplasmatic lesions and to identify the correlation among tumor location in the bronchial tree, type of growth and histological type. Fiberoptic bronchoscopy performed in 585 patients revealed lesions suspected of being malignant in 415 patients (70.9%). Our investigations revealed 38.5% of cases of intrabronchial mass. Intramural growth was observed in 15.9% of patients. Indirect signs of neoplasmatic process, like deformation or external compression of bronchus, were noted in 16.6% of cases. In 297 patients the diagnosis of lung cancer was confirmed by histopathological examination of specimens collected during fiberoptic bronchoscopy. Neoplasmatic process was not confirmed in 21 patients with intrabronchial mass and intramural growth and in any patient with symptoms of bronchial external compression. 50.8% of squamous cell cancer cases, 25.5% of small cell lung cancer cases, 20.5% of adenocarcinoma and 2.7% of giant cell carcinoma cases were diagnosed. There was no statistically significant correlation among tumor location in the bronchial tree, type of growth and histological type of lung cancer.